(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
Gynecological diseases encompass a broad range of conditions that significantly impact women’s health and well-being. This article provides an overview of essential concepts related to common gynecological disorders, including uterine fibroids, endometriosis, polycystic ovary syndrome (PCOS), cervical cancer, and others. It outlines key diagnostic methods used to identify these conditions, discusses various treatment options ranging from conservative management to surgical intervention, and emphasizes the importance of preventative measures. Preventative strategies include regular screenings, lifestyle modifications, vaccination, and awareness of risk factors. The aim of this paper is to provide a comprehensive understanding of gynecological diseases, promoting early detection, effective management, and proactive prevention to improve women’s health outcomes.